Estimating the number of people in a particular area using WiFi [WiFi Ile Belirli Bir Alandaki Insan Sayisini Tahmin ETME] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
There is a number of ways to estimate the number of people in a particular area. From image processing to movement pattern analysis, the sheer number of methods exist in the literature. An interesting one among these methods is the one estimating with the use of signal processing. Because it is much cheaper compared to the other methods in the literature, it is more commonly implemented. In this study, the number of people in a particular area is estimated by analyzing the WiFi signals captured from mobile devices. © 2015 IEEE.
Keywords: Estimating the number of people; WiFi; Wireless network